MODIFIKASI PROTOKOL AODV-BR MENGGUNAKAN LINK EXPIRATION TIME (LET) UNTUK MENINGKATKAN STABILITAS LINK DI LINGKUNGAN MOBILE Ad-Hoc NETWORK (MANET) - Rachmat Rachmat; Supeno Djanali; Radityo Anggoro (JUTI: Jurnal Ilmiah Teknologi Informasi, 2017)
AODV protocol is a protocol that is fairly mature in mobile Ad-Hoc network. But the traditional AODV protocol in some ways it seems less satisfying, especially on the stability of data transmission. Development continues, one of which AODV-Backup Routing which became known AODV-BR, were present to address the stability issues of data delivery by providing a backup route, however, AODV-BR still use traditional routing paths that are vulnerable to termination due to the formation of these calculations are based on minimum hop. This study proposes a modified AODV-BR with reliability be the ability to build main route and to choose the route up to the value of the highest stability was then called AODV-Stable bacukp Routing (AODV-SBR). Armed algorithms Link Expiration Time with node movement calculation technique, so the AODV-SBR is able to calculate the value of the minimum and maximum connectivity nodes in a route as the main reference in establishing a delivery route data more stable. The results test of the both protocols in Packet Delivery Ratio (PDR), Throughput, End-to-En Delay and Routing Overhead shows that performance of AODV-SBR better than AODV-BR